Assessment of foliar dust deposition and elemental concentrations in foliar dust and long rows of grand tamarind leaves along two major roads of Coimbatore, India. (February 2021) - Subpiramaniyam, Sivakumar; Boovaragamoorthy, Gowri Manogari; Kaliannan, Thamaraiselvi; Krishna, Kadirvelu; Hong, Sung-Chul; Yi, Pyong-In; Jang, Seong-Ho; Suh, Jeong-Min
Abstract: In this study, the concentration of foliar dust and 23 elemental concentrations in foliar dust and foliar tissues were studied using long rows of grand tamarind trees grown in two major roads in Coimbatore, India. Twenty-four sampling sites were chosen and categorized as urban (n = 5), suburban (n = 14), and rural (n = 5) areas based on the local population. In the case of foliar dust concentration, a significant difference was noted between the sites of urban (range between 3.06 and 6.68 μ/cm 2 ) and suburban areas (range between 0.56 and 5.75 μ/cm 2 ) but not for rural areas (range between 0.40 and 0.47 μ/cm 2 ). When comparing the urban, suburban, and rural, either significantly or insignificantly, 17 elements (Al, Ba, Bi, Ca, Cd, Co, Cu, Fe, Ga, In, K, Mg, Mn, Ni, Sr, and Zn) in urban and five elements (Ag, B, Cr, Na, and Pb) in suburban were higher. However, in the case of elements in tamarind laves, almost all elements except Na and K were higher in the urban area. Furthermore, the study results suggest that the elements in both foliage dust and in tamarind leaves are not evenly distributed between the sites of urban, suburban, and rural areas. This uneven distribution might be due to the construction being performed on a stretch of a four-lane highway during sampling, heavy transportation in three small junctions of suburban sites, and a rail over-bridge construction in one suburban site. However, comprehensive studies are needed to confirm this conclusion. Graphical abstract: Image 1 Highlights: Long rows of grand tamarind leaves were used to collect dust concentrations. Samples were categorized within urban, suburban, and rural areas. Elements were tested in foliar dust and tamarind leaves. Many elements in foliar dust and in tamarind leaves were higher in urban areas. Elements in all samples are not evenly distributed between the sites.